7x-(5x+13)=9-(2x-7)

Simple and best practice solution for 7x-(5x+13)=9-(2x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-(5x+13)=9-(2x-7) equation:



7x-(5x+13)=9-(2x-7)
We move all terms to the left:
7x-(5x+13)-(9-(2x-7))=0
We get rid of parentheses
7x-5x-(9-(2x-7))-13=0
We calculate terms in parentheses: -(9-(2x-7)), so:
9-(2x-7)
determiningTheFunctionDomain -(2x-7)+9
We get rid of parentheses
-2x+7+9
We add all the numbers together, and all the variables
-2x+16
Back to the equation:
-(-2x+16)
We add all the numbers together, and all the variables
2x-(-2x+16)-13=0
We get rid of parentheses
2x+2x-16-13=0
We add all the numbers together, and all the variables
4x-29=0
We move all terms containing x to the left, all other terms to the right
4x=29
x=29/4
x=7+1/4

See similar equations:

| (3x+28)^1/2=x+8 | | 15-p=10 | | x/12+3x/6=3/4 | | x/360=4/20 | | 4(3x-4)-3=4(x-4)+13 | | 3q-(8q+13)=7-(8q-2) | | 15(15+x)=8^2 | | (5x+1)(8x-20)=180 | | 900=x^2+80x | | (9x-77)(3x+7)=180 | | 9x-773x+7=180 | | 80=-v+272 | | .25(24x+12)=6(x+.5) | | 227-w=87 | | -10=-7+x/2 | | 11+x+46=180 | | 15.9=r^2 | | -14p=70 | | 2x+-2=x+10 | | 72x+60=72x-9 | | -2+2x=10+x | | (2x)^2-8=0 | | 92x0^2-8=0 | | (3-8y)•(-2.5)=y | | 6-2(3x-4)=-10x= | | 9.1+v/7=-2.1 | |  8r^2-2r-3=0  | | 12(x+3=-3(x+13) | | 10^(x+5)-8=60 | | 37+x=90 | | 9x-18/6=3x+18/10 | | a-16=-45 |

Equations solver categories